GUIDED WRITING ACTIVITIES IN TEACHING WRITING TO SEVENTH GRADE STUDENTS OF MTsN WATULIMO TRENGGALEK - Kusmiana, Linda (Lingua Scientia, 2013)
Â Abstract : Guided Writing Activities is a strategy of teaching writing in which the teacher and the students cooperate in classroom activity. the teacher manages the classroom situation in order to keep students active and reach the topic target by preparing guided question. It can help the students to show their idea or thought to write.In the context of school, using guided writing activities students were given guided question from teacher to stimulate their words to develop writing skill.The students were given time 80 minutes to write descriptive text based on guide question that provided by the teacher.The purpose of the study are to: 1) Find out the students writing score before being taught applying guided writing activities 2) Find out the students writing score after being taught applying guided writing activities 3) Find out significance different score before and after being taught applying guided writing activities. The research design employed is pre- experimental design. The result shows that the total of studentsâ scores before being taught applying guided writing activities are 2479, while the total score after being taught applying guided writing activities are 2811. The T- score is 6.695, whereas T- table with significance level 5% is 1.697. Therefore, T- score is greater than T- table. This means that Ha which states that teaching using guided writing to improve studentâs achievement in writing of seventh grade students of MTsN Watulimo is effective used.Â Keywords: effectiveness, guided writing activities, writing achievement